Unnatural Enhancements - Jensen, Steven J. (Irish theological quarterly, 2018)
This paper claims that the distinction between therapy and enhancement, which has played a significant role in the discussion of the moral implications of human enhancements, is of only secondary and subordinate importance. Of much greater importance is the distinction between natural and unnatural enhancements, or rather between natural and unnatural means of enhancing. After briefly indicating the moral significance of the distinction between what is natural and unnatural, the paper focuses on the difficult task of discriminating between those means of enhancing that are natural and those that are unnatural.